2014
DOI: 10.1038/bjc.2014.210
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of EGFR with KRAS, or BRAF, or PIK3CA somatic mutations in lung cancer: a comprehensive mutation profiling from 5125 Chinese cohorts

Abstract: Background:Determining the somatic mutations of epidermal growth factor receptor (EGFR)-pathway networks is the key to effective treatment for non-small cell lung cancer (NSCLC) with tyrosine kinase inhibitors (TKIs).The somatic mutation frequencies and their association with gender, smoking history and histology was analysed and reported in this study.Methods:Five thousand one hundred and twenty-five NSCLC patients' pathology samples were collected, and EGFR, KRAS, BRAF and PIK3CA mutations were detected by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
170
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 203 publications
(201 citation statements)
references
References 35 publications
24
170
3
1
Order By: Relevance
“…The incidence of PIK3CA mutation was around 3% in lung adenocarcinoma and 5–10% in squamous cell carcinoma 12, 13, 14, 15. In this study, the frequency of PIK3CA mutation at 2.8% was consistent with that of previous studies.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The incidence of PIK3CA mutation was around 3% in lung adenocarcinoma and 5–10% in squamous cell carcinoma 12, 13, 14, 15. In this study, the frequency of PIK3CA mutation at 2.8% was consistent with that of previous studies.…”
Section: Discussionsupporting
confidence: 91%
“…Mutation in PIK3CA signaling pathways may induce resistance to EGFR‐TKIs of lung cancer patients. Although reported in previous studies, treatment and efficacy data of patients harboring PIK3CA mutations were not available 12, 13. The results of a meta‐analysis showed that PIK3CA mutation adversely affected the clinical efficacy and OS of NSCLC patients on EGFR‐TKIs 14.…”
Section: Discussionmentioning
confidence: 99%
“…BRAF p.V600E mutation is more frequent in females 52,54 and never smokers 54 in some studies, but several studies failed to show these associations. 49,50,53,58 One distinction between BRAF mutations and other Figure 1 Forest plot of sensitivity and specificity for immunohistochemistry (IHC)-based determination of ROS1 rearrangement positivity compared with fluorescence in situ hybridization.…”
Section: Expert Consensus Opinionmentioning
confidence: 99%
“…FN, false-negative; FP, false-positive; TN, true-negative; TP, true-positive. jmd.amjpathol.org -The Journal of Molecular Diagnostics targetable oncogenes is that non-p.V600E BRAF mutations (particularly the exon 11 mutations) may coexist with mutations in KRAS, 49,52,53,59 whereas the p.V600E mutations are mutually exclusive of KRAS, EGFR, or ALK alterations.…”
Section: Expert Consensus Opinionmentioning
confidence: 99%
See 1 more Smart Citation